Emerging Nanotechnology in Non-Surgical Periodontal Therapy in Animal Models: A Systematic Review - Adrian Brun; Nicolas Moignot; Marie-Laure Colombier; Elisabeth Dursun (Nanomaterials, 2020)
Periodontitis is one of the most prevalent inflammatory diseases. Its treatment, mostly mechanical and non-surgical, shows limitations. The aim of this systematic review was to investigate the effect of nanoparticles as a treatment alone in non-surgical periodontal therapy in animal models. A systematic search was conducted in Medline/PubMed, Web of Science, The Cochrane Library and Science Direct. The eligibility criteria were: studies (i) using nanoparticles as chemotherapeutic agent or as delivery system; (ii) including preclinical controlled animal model (experimental periodontitis); (iii) reporting alveolar bone loss; (iv) written in English; and (v) published up to June 2019. Risk of bias was evaluated according to the SYstematic Review Centre for Laboratory Animal Experimentation. On the 1324 eligible studies, 11 were included. All reported advantages in using nanoparticles for the treatment of periodontitis, highlighted by a reduction in bone loss. Agents modulating inflammation seem to be more relevant than antibiotics, in terms of efficiency and risk of antibiotic resistance. In addition, poly(lactic-co-glycolic acid) or drugs used as their own carrier appear to be the most interesting nanoparticles in terms of biocompatibility. Risk of bias assessment highlighted many criteria scored as unclear. There are encouraging preclinical data of using nanoparticles as a contribution to the treatment of periodontitis.